Excess heart age in adult outpatients in routine HIV care. (1st October 2019) - Thompson-Paul, Angela M.; Palella, Frank J.; Rayeed, Nabil; Ritchey, Matthew D.; Lichtenstein, Kenneth A.; Patel, Deesha; Yang, Quanhe; Gillespie, Cathleen; Loustalot, Fleetwood; Patel, Pragna; Buchacz, Kate
Abstract : Objective: Cardiovascular disease (CVD) is a common cause of morbidity and mortality among persons living with HIV (PLWH). We used individual cardiovascular risk factor profiles to estimate heart age for PLWH in medical care in the United States. Design: Cross-sectional analyses of HIV Outpatient Study (HOPS) data Methods: Included in this analysis were participants aged 30–74 years, without prior CVD, with at least two HOPS clinic visits during 2010–2017, at least 1-year of follow-up, and available covariate data. We calculated age and race/ethnicity-adjusted heart age and excess heart age (chronological age − heart age), using a Framingham risk score-based model. Results: We analyzed data from 2467 men and 619 women (mean chronologic age 49.3 and 49.1 years, and 23.6% and 54.6% Non-Hispanic/Latino black, respectively). Adjusted excess heart age was 11.5 years (95% confidence interval, 11.1–12.0) among men and 13.1 years (12.0–14.1) among women. Excess heart age was seen among all age groups beginning with persons aged 30–39 years [men, 7.8 (6.9–8.8); women, 7.7 (4.9–10.4)], with the highest excess heart age among participants aged 50–59 years [men, 13.7 years (13.0–14.4); women, 16.4 years (14.8–18.0)]. More than 50% of participants had an excess heart age of at least 10 years. Conclusions: Excess heart age is common among PLWH, begins in early adulthood, and impacts both women and men. Among PLWH, CVD risk factors should be addressed early and proactively. Routine use of the heart age calculator may help optimize CVD risk stratification and facilitate interventions for aging PLWH.